(untitled) (Czech Journal of International Relations, 1997)
Seven years ago, many pranksters slyly asked their targets if they knew what is the unit of timeliness. "Well, one always" they answered. Today we not only know that the mentioned "furt" meant 23 years, but we also have at our disposal a thorough and detailed documentation about the stay and removal of the Soviet troops, which occupied our country since that fateful night in April 1968. The occupation was ended by a historically social period in our country and in the world at the end of the 1980s, and the stay of the occupying troops was then ended by the significant negotiations of the post-Deslovakian post-revolutionary diplomacy, which was undoubtedly the largest and the most significant success of foreign policy. Not only experts, but also the public now have the opportunity to see for themselves.